Preparation And Characterization Of Poly(Butylene Succinate)/ Poly(Butylene Adipate-Coterephthalate) Organo-Clay Nanocomposites - Chieng, Buong Woei (2010)

(untitled)
The present research aims at studying the influence of organoclay on the properties of poly(butylene succinate)/poly(butylene adipate-co-terephthalate), PBS/PBAT blend. The organoclay was modified via cation exchange method using organic surfactants; protonated octadecylamine (ODA), cetyltrimethylammonium (CTA) and dimethyldioctadecylammonium (DDOA). The characterizations of organoclays were carried out by the Fourier Transform Infrared spectroscopy (FTIR), X-ray diffraction (XRD) and Thermogravimetric analysis (TGA). XRD and FTIR results indicated sodium montmorillonite (Na-MMT) was successfully modified to be organoclay through cation exchange method. XRD showed that the basal spacing of clay increased with the formation of organoclays. The PBS/PBAT blends were successfully prepared by melt blending technique. FTIR spectra revealed that the blends involved only physical interaction. Tensile strength and modulus decreased as the PBAT contents increased. SEM of the PBS/PBAT clearly demonstrated a two-phase morphology, which indicated the immiscibility of the components. The PBS/PBAT nanocomposites were prepared by melt intercalation technique. The expansion of the basal spacing of the clay indicated the formation of intercalated as well as exfoliated types of nanocomposites which supported by XRD diffractograms and TEM images. FTIR spectra showed that there is strong interaction between clay and PBS/PBAT polymer matrix which gives rise to improvement in tensile properties. Tensile modulus increased with clay loading up to 7 wt% while improvements in tensile strength were limited. Tensile strength increased up to 1 wt% of clay while elongation at break decreased with the addition of clay. The thermogravimetric analysis showed the presence of clays give significant improvement in thermal stability, particularly organoclay. The DMA analysis showed an increase in the storage modulus and loss modulus with the addition of organoclay into PBS/PBAT blend compared with neat PBS/PBAT. Furthermore, the presence of organoclay influenced the morphology of the PBS/PBAT blend which showed more homogeneous and single phase morphology. This revealed that the organoclay acts as compatibilizer for the immiscible PBS/PBAT polymer blend. Biodegradability results indicated that nanocomposites exhibit the same or a higher level of biodegradability compared with the PBS/PBAT blend.